Komunikasi Antar Budaya: Studi Kasus Komunikasi Komunitas Yahudi di Jakarta - Thereen Arlie; Eko Harry Susanto; Doddy Salman (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
Abstract— The Jews were descendants of Mr. Abraham, The Father of Isaac, and Jacob or known as Israel because Jacob prevailed during the struggle with God until his name was no longer Jacob but Israel. The Jews had a difficult time being made slaves by the Egyptians, oppressed by the Neo-Assyrian empire, and the Babylonian empire which led to the exile of the Jews from their homeland and enslaved, even got slaughtered by Hitler with the Nazis during world war II. This is what made the Jews move because they had nowhere to live. The arrival of Jews in Indonesia has been around since the Sriwijayan kingdom, they came as merchants and have inhabited the Indonesia for a long time. People of Jewish descent in Indonesia have a total of about 5000 people excluding Maluku which is up to 500,000 in number. In Indonesia there is a community for people of Jewish descent and Judaism namely The United Indonesian Jewish Community (UIJC) which was formed in 2010. Therefore, the author discusses whether the UIJC community has relations with Indonesian society or vice versa because Indonesia is the country with the largest Muslim population in the world. The methodology of this research is qualitative through case study method based on the results of data from informants / resource persons who have an impact on this research. Based on the interview, UIJC does not get negative stigma from the society. Keywords—: Jewish; Judaism; Community.